2009
DOI: 10.1007/s11999-009-0800-3
|View full text |Cite
|
Sign up to set email alerts
|

Type of Hip Fracture Determines Load Share in Intramedullary Osteosynthesis

Abstract: The choice of the appropriate implant continues to be critical for fixation of unstable hip fractures. Therefore, the goal of this study was to develop a numerical model to investigate the mechanical performance of hip fracture osteosynthesis. We hypothesized that decreasing fracture stability results in increasing load share of the implant and therefore higher stress within the implant. We also investigated the relationship of interfragmentary movement to the fracture stability. A finite element model was dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 32 publications
3
49
0
6
Order By: Relevance
“…The specimens were then prepared for biomechanical testing in a single leg loading configuration (Eberle et al, 2009). The distal end of each femur was potted with casting resin (RENCAST FC53, Huntsman Advanced Materials, Bergkamen, Germany) in an aluminum case that fitted into a cardan joint.…”
Section: In-vitro Experimentsmentioning
confidence: 99%
“…The specimens were then prepared for biomechanical testing in a single leg loading configuration (Eberle et al, 2009). The distal end of each femur was potted with casting resin (RENCAST FC53, Huntsman Advanced Materials, Bergkamen, Germany) in an aluminum case that fitted into a cardan joint.…”
Section: In-vitro Experimentsmentioning
confidence: 99%
“…Based on a study by Eberle et al, 12 the force vector was pointing laterally in the coronal plane at an angle of 138 with the axis of the femoral shaft. In the sagittal plane, it was pointing posteriorly at an angle of 88 with the shaft axis.…”
mentioning
confidence: 99%
“…Furthermore, specimens were stripped of soft tissue and ligaments to produce a standardised osteotomy and simplify the experimental setup. It has been demonstrated that the effect of additional muscle forces on stress distribution in implants is negligible [43]. Load was therefore applied in the vertical direction and forces produced by hip abduction or physiological gait were not taken into account.…”
Section: Limitationsmentioning
confidence: 99%